PENGARUH PELATIHAN, IKLIM ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS KESEHATAN KOTA TANJUNGBALAI - Novi Sriana; Sri Mulyani Rahimah; Agung Hasan Sadikin; Ferdinan Pendiangan; Riccy Sauty (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study are: How the influence of training, organizational climate and work environment on the work performance at Dinas Kesehatan Kota Tanjungbalai. This study aims to determine the effect of training, organizational climate and work environment on employee work performance. With the total sampling technique, the sample in this study was 48 people. The results showed; Partial training has a positive effect on employee work performance of 4,828; Organizational climate partially has a positive influence on employee work performance of 3.467; The work environment partially has a positive influence on employee work performance of 3,311; Training, organizational climate and work environment simultaneously have a positive and significant influence on employee work performance of 37.865.